Tailoring Anchoring Groups in Low‐Dimensional Organic Semiconductor‐Incorporated Perovskites. Issue 3 (25th January 2022) - Liang, Aihui; Ma, Ke; Gao, Yao; Dou, Letian
Abstract : Low‐dimensional, organic semiconductor‐incorporated perovskites (OSiPs) are hybrid structures with functional organic cations intercalated between inorganic octahedron frameworks. They exhibit increased structural and compositional tunability, fascinating electronic properties, and enhanced stability for a wide range of applications. Currently, the interactions between the conjugated organic building blocks and the metal halide inorganic building blocks have not been fully investigated. Herein, a series of bithiophene‐based conjugated ligands with formamidinium, imidazolium, and benzimidazolium terminal groups to examine the influence of different anchoring groups on the crystal structures, phase formation, and device performances are reported. It is shown that the terminal groups of the ligands have significant effect on the interactions between ligands and octahedra in perovskites, thus determine the formation of the crystal structures. Only the 3D perovskite solar cells passivated by the ligands with imidazolium and benzimidazolium terminal groups exhibit enhancement in power conversion efficiencies as well as reduced hysteresis. A new strategy is provided for designing novel OSiPs structures and functionalities via tailoring the anchoring group. Abstract : A series of bithiophene‐based conjugated ligands with formamidinium, imidazolium, and benzimidazolium terminal groups are synthesized to examine the influence of different anchoring groups on the crystal structures, phase formation, and device performances. Perovskite solar cells passivated by the low‐dimensional OSiPs containing benzimidazolium cations exhibit enhanced power conversion efficiencies and reduced hysteresis.